Implementasi Konsep Marketing 5.0 dalam Strategi Pemasaran UMKM: Studi Kasus pada Adaptasi Teknologi dan Human-Centered Approach - Baskara, Andika; Nurhayati, Nurhayati; Firdaus, Firdaus (Jurnal EMT KITA, 2026)
This study aims to explore the application of the Marketing 5.0 concept in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a focus on the challenges and strategies faced in adopting advanced technology in digital marketing. This study employs a descriptive–qualitative approach using a case study design in the city of Semarang, the research involved 10 participants (business owners, marketing managers, and digital marketing staff). Using thematic analysis, the study identifies key themes, including the adoption of basic digital technologies as the foundation of marketing; early use of AI such as customer service chatbots and automated product recommendations; utilisation of simple analytics from social media and e-commerce platforms to map consumer behaviour; and the strengthening of human-centred approaches through storytelling and personalised content. Practical examples include the use of simple IoT tools for stock monitoring and Instagram insights to determine optimal posting times. The findings reveal that major challenges, limited digital infrastructure, low technological literacy, and constrained human resources can be addressed through gradual technology adoption and external support, particularly government-led digital training and technical assistance from technology companies. The study underscores that a mindset shift towards greater openness to technology is essential for MSMEs to fully harness the potential of Marketing 5.0.